Inhibition of AcrAB-TolC enhances antimicrobial activity of phytochemicals in Pectobacterium brasiliense - Pun, Manoj; Khazanov, Netaly; Galsurker, Ortal; Kerem, Zohar; Senderowitz, Hanoch; Yedidia, Iris (Frontiers in Plant Science, 2023)
The eons-long co-evolvement of plants and bacteria led to a plethora of interactions between the two kingdoms, in which bacterial pathogenicity is counteracted by plant-derived antimicrobial defense molecules. In return, efflux pumps (EP) form part of the resistance mechanism employed by bacteria to permit their survival in this hostile chemical environment. In this work, we study the effect of combinations of efflux pump inhibitors (EPIs) and plant-derived phytochemicals on bacterial activity using Pectobacteriun brasiliense 1692 (Pb 1692) as a model system. Specifically, we measured the minimal inhibitory concentration (MIC) of two phytochemicals, phloretin (Pht) and naringenin (Nar), and of one common antibiotic ciprofloxacin (Cip), either alone or in combinations with two known inhibitors of the aAcrB EP of Escherichia coli, a close homolog of the AcrAB-TolC EP of Pb 1692. In addition, we also measured the expression of genes encoding for the EP, under similar conditions. Using the FICI equation, we observed synergism between the EPIs and the phytochemicals, but not between the EPIs and the antibiotic, suggesting that EP inhibition potentiated the antimicrobial activity of the plant-derived compounds, but not of Cip. Docking simulations were successfully used to rationalize these experimental results. Our findings suggest that AcrAB-TolC plays an important role in the survival and fitness of Pb1692 in the plant environment and that its inhibition is a viable strategy for controlling bacterial pathogenicity.